Hexa Helix’s Collaboration in Creative Economy Development Based on Local Wisdom: Case Study of Ikat Weaving MSMEs in Kupang City (Jurnal Bina Praja, 2024)
Indonesia's creative economy has experienced notable growth, contributing Rp1,105 trillion in 2018. Among its integral components, ikat weaving plays a crucial role in sustaining production, preserving traditions, and maintaining product authenticity. The sector encourages innovation, adoption of digital technology, and benefits from government policies supporting creative industries. Despite its international recognition, traditional ikat weaving faces significant challenges for MSMEs, including capital constraints, marketing difficulties, and limited human resources. Preserving ikat weaving in Kupang City presents multifaceted challenges encompassing social, economic, and market dynamics. This qualitative research employed a case study approach to delve into these complexities. Case study research involves in-depth data collection from various sources like interviews, observations, and documents, aiming to reveal insights into real-life scenarios. The study underscores the pivotal role of Hexa Helix collaboration involving government, business, universities, NGOs, mass media, and the affected community in advancing ikat weaving. This collaborative framework promotes innovation, facilitates resource sharing, and enhances community engagement. However, challenges identified in governance and administration aspects highlight the informal nature of current cooperation efforts. Despite these challenges, the research demonstrates that three other dimensions of successful collaboration—autonomy, mutuality, and reciprocity—are effectively contributing to the development of ikat weaving MSMEs in Kupang City. This collaborative approach is pivotal in safeguarding ikat weaving as a cultural heritage while unlocking its economic potential. The findings suggest opportunities for stakeholders to enhance collaboration through more structured and formal mechanisms. By addressing governance and administrative challenges, stakeholders can better support ikat weaving MSMEs, ensuring sustainable growth and cultural preservation.
Keywords: Hexa Helix; Collaboration; Creative Economy Development; Ikat Weaving; MSMEs